Schistosomiasis mansoni: an analysis of epidemiological indicators in the City of São Luís, Maranhão, Brazil (Research, Society and Development, 2020)
Schistosomiasis mansoni (MS) is a parasitic disease caused by the etiological agent of the genus Schistosoma. Worldwide, 290 million people are infected with schistosomes, mainly S. haematobium and S. mansoni. In Brazil, it is one of the most relevant parasitic endemic diseases and its occurrence is maintained due to deficiencies in basic sanitation and environmental education among the population. This study aimed to carry out an analysis of epidemiological indicators in the city of São Luís, Maranhão, Brazil. For this, a documentary research of these MS indicators was carried out in the chosen municipality. The time frame chosen for the research was from 2006 to 2016. The data used were extracted from the Schistosomiasis Control Program (PCE). It was found that 2006 had the highest number of exams performed (n = 50073) followed by 2012 (n = 23688). In 2009, 123 (2.83%) positive cases were registered, followed by 2007 with 101 (2.28%) and 2006 with 84 (0.17%) confirmed cases. The low parasitic load (1 to 4 eggs) represented 86% of all cases, with treatment coverage above 98% among all infected individuals. Thus, it was possible to verify that the number of positive cases for MS has reduced substantially in recent years. However, despite the fact that São Luís has reduced the number of positive cases, mainly, in the last three years analyzed, the epidemiological indicators evaluated prove that this parasitosis remains a serious public health problem.